The metaphor of the Divine as Planter of the people : stinking grapes or pleasant planting? - Pantoja, Jennifer Metten. (Biblical Interpretation Series, 2017)
In The Metaphor of the Divine as Planter of the People Jennifer Metten Pantoja traces the emergence of the conceptual metaphor YHWH IS THE PLANTER OF THE PEOPLE in ancient Hebrew poetry and follows its development throughout biblical history and Second Temple literature, in order to illustrate how the deep connection to the land shaped ancient thought and belief. Within this broader, primary metaphor, the complex metaphor YHWH IS THE VINTNER OF ISRAEL is also analyzed as an image predominant in the pre-exilic prophetic literature. Recent advances in cognitive linguistics, coupled with traditional historical-critical methods, as well as a survey of the material culture, work in tandem to illuminate one snapshot of ancient Israel's conception of the divine.